Long term outcome of Ph+ CML patients achieving complete cytogenetic remission with interferon based therapy moving from interferon to imatinib era. Issue 2 (February 2014) - Malagola, Michele; Breccia, Massimo; Skert, Cristina; Cancelli, Valeria; Soverini, Simona; Iacobucci, Ilaria; Cattina, Federica; Liberati, Anna Maria; Tiribelli, Mario; Annunziata, Mario; Trabacchi, Elena; De, Antonio; et al.
<x xml:space="preserve">Abstract</x> Interferon α (IFNα) prolongs survival of CML patients achieving CCyR and potentially synergizes with TKIs. We report on the molecular status and long term outcome of 121 patients who were treated in Italy between 1986 and 2000 with IFNα based therapy and who obtained CCyR. After a median follow up of 16.5 years, 74 (61%) patients were switched to standard imatinib: 48 (65%) lost the CCyR on IFNα, and 36 (75%) are alive and in CCyR; 26 (35%) were switched to imatinib when they were still in CCyR on IFNα, and all 26 are alive and in CCyR. Forty‐seven patients (39%) were never switched to imatinib: 24 (51%) continued and 23 (49%) discontinued IFNα, respectively, and 39/47 (83%) are alive and in CCyR. At last follow‐up, the BCR‐ABL transcripts level was available in 96/101 living patients (95%) The BCR‐ABL:ABL ratio was between 0.1 and 0.01% (MR3.0) in 17%, and less than 0.01% (MR4.0) in 81% of patients. No patient was completely molecular negative (MR4.5 or MR5.0). The OS at 10 and 20 years is 92 and 84%, respectively. This study confirms that CCyR achieved with IFNα and maintained with or without imatinib or any other therapy significantly correlates with long term survival in CML patients who mostly have MR4.0. Complete molecular response (MR4.5 or MR5.0) seems to be unnecessary for such a long survival. This study further supports development of studies testing the clinical effect of the combinations of TKIs with IFNα. Am. J. Hematol. 89:119–124, 2014. © 2013 Wiley Periodicals, Inc.